A new application of generalized quasipower increasing sequences - Bor, H. (Український математичний журнал, 2012)
We prove a theorem on ∣ N¯,pn,θn ∣k-summability by using a new general class of power increasing sequences instead of a quasi-η-power increasing sequence. This theorem also includes some new and known results.